2017
DOI: 10.1007/s10067-017-3874-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety in rheumatoid arthritis patients and their associations with serum vitamin D level

Abstract: Vitamin D deficiency may be associated with depression in the general population. This study aimed to describe the prevalence of depression and anxiety in rheumatoid arthritis (RA) patients from Northwestern China and identify associations of Hamilton Depression Scale (HAMD) and Hamilton Anxiety Scale (HAMA) scores with serum vitamin D level in these patients. We recruited 161 RA patients inform the First Affiliated Hospital of Xi'an Jiaotong University during Nov. 2016 to Feb. 2017. All patients completed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…There have been many studies exploring the potential associations between vitamin D and psychological phenomena or psychiatric disorders, including depression (Alavi, Khademalhoseini, Vakili, & Assarian, 2018; Amini, Jafarirad, & Amani, 2018; Bertone‐Johnson et al, 2012; Dumville et al, 2006; Ghaderi et al, 2017; Jorde, Sneve, Figenschau, Svartberg, & Waterloo, 2008; Khoraminya, Tehrani‐Doost, Jazayeri, Hosseini, & Djazayery, 2013; Pittampalli et al, 2018), anxiety (Armstrong et al, 2007; Huang et al, 2014; Pu et al, 2018), psychotic disorders (Chiang, Natarajan, & Fan, 2016), cognitive impairment (Degner, 2016; Etgen, Sander, Bickel, Sander, & Forstl, 2012), sleep disturbance (Gao et al, 2018; Ghaderi et al, 2017), autism spectrum disorder (Moradi et al, 2018; Patrick & Ames, 2014), and substance use (Ghaderi et al, 2017). Studies investigating the relationship between vitamin D and depression are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies exploring the potential associations between vitamin D and psychological phenomena or psychiatric disorders, including depression (Alavi, Khademalhoseini, Vakili, & Assarian, 2018; Amini, Jafarirad, & Amani, 2018; Bertone‐Johnson et al, 2012; Dumville et al, 2006; Ghaderi et al, 2017; Jorde, Sneve, Figenschau, Svartberg, & Waterloo, 2008; Khoraminya, Tehrani‐Doost, Jazayeri, Hosseini, & Djazayery, 2013; Pittampalli et al, 2018), anxiety (Armstrong et al, 2007; Huang et al, 2014; Pu et al, 2018), psychotic disorders (Chiang, Natarajan, & Fan, 2016), cognitive impairment (Degner, 2016; Etgen, Sander, Bickel, Sander, & Forstl, 2012), sleep disturbance (Gao et al, 2018; Ghaderi et al, 2017), autism spectrum disorder (Moradi et al, 2018; Patrick & Ames, 2014), and substance use (Ghaderi et al, 2017). Studies investigating the relationship between vitamin D and depression are the most common.…”
Section: Introductionmentioning
confidence: 99%
“…This is because patients suffering from RA show distinct changes in their quality of life that are caused not only by direct effects of the underlying disease but also by different psychological factors [2]. Accordingly, a reduced quality of life and a high prevalence of anxiety and depression can be observed in RA patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…However the difference was not significant. Conflicting results have been reported as some studies have demonstrated a strong relationship between vitamin D and depression (8,(15)(16)(17) whereas others have shown no association (9,18,19). In Netherlands, Milaneschi Y, et al reported a significant correlation between vitamin D level and depressive symptoms at a two-year follow up (20).…”
Section: Discussion:-mentioning
confidence: 99%